1999
DOI: 10.1159/000010096
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar Organizer Regions in Differentiated Preneoplastic and Neoplastic Endometrial Lesions

Abstract: The aim of the study was the quantitative assessment of nucleolar organizer regions (NORs) in the cells of preneoplastic and neoplastic endometrial lesions. Retrospective analysis included tissue material obtained from 87 patients with simple and complex hyperplasia with or without atypia and well-differentiated stage-I endometrial adenocarcinoma. Sections were made from routine paraffin blocks and stained with AgNO3. The mean number of AgNORs per cell was determined. The results obtained indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…AgNOR area and AgNOR areacount ratio are the most valuable features for differential diagnosis of normal, preneoplastic, and cancer cells. The average values of AgNOR showed an increased tendency according to the neoplastic changes of the nasopharyngeal epithelia that was concordant with the change of AgNOR from normal to hyperplastic lesions and carcinoma in endometrial samples 13,14 and from normal to dysplastic lesions and carcinoma in gastric biopsy specimens 17 and in esophageal samples. 18 However, overlap was found between AgNOR values in SE and in DC in this study that was also found between AgNOR values in normal, ordinary hyperplastic, and neoplastic breast lesions.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…AgNOR area and AgNOR areacount ratio are the most valuable features for differential diagnosis of normal, preneoplastic, and cancer cells. The average values of AgNOR showed an increased tendency according to the neoplastic changes of the nasopharyngeal epithelia that was concordant with the change of AgNOR from normal to hyperplastic lesions and carcinoma in endometrial samples 13,14 and from normal to dysplastic lesions and carcinoma in gastric biopsy specimens 17 and in esophageal samples. 18 However, overlap was found between AgNOR values in SE and in DC in this study that was also found between AgNOR values in normal, ordinary hyperplastic, and neoplastic breast lesions.…”
Section: Discussionsupporting
confidence: 73%
“…10,11 The AgNORs technique has been used in the investigation of preneoplastic lesions, for example, preneoplastic and neoplastic endometrial lesions. [12][13][14] The amount of NORs also reflected the rate of replicative activity of cells when formalinfixed paraffin-embedded archival neoplastic specimens were studied. After silver staining, the NORs can be easily identified as black dots exclusively localized throughout the nucleolar area and can be visualized at the light microscopic level for image analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining with MAbs is strongly correlated with grade, and high expression of Ki-67 protein has been associated with shorter progression-free survival and OS (Henriksen et al, 1994;Marx et al, 1997;Korkolopoulou et al, 2002). In one study, no appreciable difference was found in the relative intensity of Ki-67 staining among LMP and G1 tumors (Terlikowski et al, 1999), consistent with our observation that LMPs and a majority of G1 carcinomas do not express detectable levels of Ki-67, either by array profiling of by immunostaining with Ki-67 antibodies. Conversely, CDKN1A mRNA is weakly expressed or absent in G2-G3 carcinomas and low or absent levels of this protein have been correlated with high-grade, advanced FIGO stage, primary residual tumor and poor OS.…”
Section: Discussionmentioning
confidence: 98%